Can we see quantum gravity?: photons in the asymptotic-safety scenario - Döbrich, Babette; Eichhorn, Astrid (Journal of high energy physics, 2012)
In the search for a quantum theory of gravity it is crucial to find experimental access to quantum gravitational effects. Since these are expected to be very small at observationally accessible scales it is advantageous to consider processes with no tree-level contribution in the standard model, such as photon-photon scattering. We examine the implications of asymptotically safe quantum gravity in a setting with extra dimensions for this case, and point out that various near-future photon-collider setups, employing either electron or muon colliders, or even a purely laser-based setup, could provide a first observational window into the quantum gravity regime.
Gesehen am 11.01.2018